Core Signaling Pathways in Human Pancreatic Cancers Revealed by Global Genomic Analyses - Jones, Siân; Zhang, Xiaosong; Parsons, D. Williams; Lin, Jimmy Cheng-Ho; Leary, Rebecca J; Angenendt, Philipp; Mankoo, Parminder; Carter, Hannah; Kamiyama, Hirohiko; Jimeno, Antonio; Hong, Seung-Mo; Fu, Baojin; et al. (Science (American Association for the Advancement of Science), 2008)
There are currently few therapeutic options for patients with pancreatic cancer, and new insights into the pathogenesis of this lethal disease are urgently needed. Toward this end, we performed a comprehensive genetic analysis of 24 pancreatic cancers. We first determined the sequences of 23,219 transcripts, representing 20,661 protein-coding genes, in these samples. Then, we searched for homozygous deletions and amplifications in the tumor DNA by using microarrays containing probes for ~10⁶ single-nucleotide polymorphisms. We found that pancreatic cancers contain an average of 63 genetic alterations, the majority of which are point mutations. These alterations defined a core set of 12 cellular signaling pathways and processes that were each genetically altered in 67 to 100% of the tumors. Analysis of these tumors' transcriptomes with next-generation sequencing-by-synthesis technologies provided independent evidence for the importance of these pathways and processes. Our data indicate that genetically altered core pathways and regulatory processes only become evident once the coding regions of the genome are analyzed in depth. Dysregulation of these core pathways and processes through mutation can explain the major features of pancreatic tumorigenesis.